Review of theoretical methods and research aspects for detecting leaf water content using terahertz spectroscopy and imaging - Qu, Fangfang; Nie, Pengcheng; Lin, Lei; Cai, Chengyong; He, Yong (International Journal of Agricultural and Biological Engineering, 2018)
The water content in vegetative leaves is an important indicator to plant science. It reveals the physiological status of plants and provides valuable information in irrigation management. Terahertz (THz) as a state-of-the-art technology shows great potential in measuring and monitoring the water status in plant leaves. This paper reviewed the theoretical models for calculating water content in the plant leaves, the methods for eliminating the scattering loss caused by the surface roughness of leaf, the applications of THz spectroscopy and THz imaging for monitoring leaf water content and describing leaf water distribution. The survey of the researches presents the considerable advantages of this emerging and promising THz technology in agriculture.Keywords: terahertz (THz) spectroscopy, terahertz imaging, leaf water content, leaf water distribution, theoretical models, eliminating scattering loss, agricultureDOI: 10.25165/j.ijabe.20181105.3952Citation: Qu F F, Nie P C, Lin L, Cai C Y, He Y. Review of theoretical methods and research aspects for detecting leaf water content using terahertz spectroscopy and imaging. Int J Agric & Biol Eng, 2018; 11(5): 27–34.